Media Literacy and the Broadcast "Nation" - Karen Weaver (University of Kansas Libraries, 2013)
In this paper, the author provides a response to Dunn (2013) and Martin (2013). Focusing on the relationship between the media and intercollegiate sport, the author examined the impact of intercollegiate athletics on the finances, mission, and outcomes of the broader institutions in which they are housed. Recommendations for future action are offered.